2012
DOI: 10.1016/j.neuron.2011.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Deafening Drives Cell-Type-Specific Changes to Dendritic Spines in a Sensorimotor Nucleus Important to Learned Vocalizations

Abstract: Summary Hearing loss prevents vocal learning and causes learned vocalizations to deteriorate, but how vocalization-related auditory feedback acts on neural circuits that control vocalization remains poorly understood. We deafened adult zebra finches, which rely on auditory feedback to maintain their learned songs, to test the hypothesis that deafening modifies synapses on neurons in a sensorimotor nucleus important to song production. Longitudinal in vivo imaging revealed that deafening selectively decreased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 66 publications
11
74
0
Order By: Relevance
“…Several studies demonstrate key roles for mGluRs in regulating experience-dependent circuit plasticity in response to visual experience (40,41), fear conditioning (42), and somatosensory experience (9,43). Moreover, recent studies of mGluR-dependent synaptic plasticity have led to the discovery of novel cellular and molecular mechanisms with implications for diseases such as Fragile X syndrome and Alzheimer's disease (26,44,45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies demonstrate key roles for mGluRs in regulating experience-dependent circuit plasticity in response to visual experience (40,41), fear conditioning (42), and somatosensory experience (9,43). Moreover, recent studies of mGluR-dependent synaptic plasticity have led to the discovery of novel cellular and molecular mechanisms with implications for diseases such as Fragile X syndrome and Alzheimer's disease (26,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, spine elimination occurs more frequently than does spine formation in young rodents between the first and the third month of age (3)(4)(5), a period when experience-dependent refinement of neural circuitry is in its peak. Furthermore, several in vivo studies demonstrate that manipulations leading to experience-dependent circuit plasticity also increase the rate of spine shrinkage and loss (6)(7)(8)(9). However, it remains unclear how neural activity drives the selective shrinkage and loss of individual dendritic spines in response to sensory experience.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HVC-RA neurons, in particular, have been suggested to provide a metronome-like function in maintaining the precise temporal structure underlying the acoustic unfolding of the song [Hahnloser et al, 2002;Long and Fee, 2008]. At a higher-order level, it has been suggested that the vocal motor pathway more generally promotes song stability [Thompson and Johnson, 2007] relative to the anterior forebrain pathway, which in turn confers song variability [Brainard and Doupe, 2000;Nordeen and Nordeen, 2010;Tschida and Mooney, 2012]. Any of these roles is consistent with the idea that more HVC-RA neurons may correspond to greater song stability.…”
Section: New Neurons In the Song Motor Pathway Hvc: A Role For New Nementioning
confidence: 99%
“…It has been shown that deafening adult songbirds decreases the amplitude of spontaneous synaptic activity, alters spontaneous action potential activity in HVC X neurons, and selectively decreases their dendritic spine sizes and stability (Tschida and Mooney, 2012). These changes precede and predict subsequent birdsong degradation.…”
Section: Introductionmentioning
confidence: 99%